PENINGKATAN KOMPETENSI GURU MELALUI MODEL PELATIHAN BERBASIS LESSON STUDY: STUDI PADA GURU MI - Yana, Hawwin Huda (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2024)
ABSTRACT Teacher competence is a key element in determining the quality of learning, especially in Madrasah Ibtidaiyah (MI), which plays a strategic role in shaping students’ character and intelligence from an early age. However, there remains a gap between the ideal competencies of teachers and the realities in the field, particularly in lesson planning, classroom management, and reflective practice. This study aims to examine the effectiveness of a lesson study-based training model in improving the professional competence of MI teachers. The research employed a descriptive qualitative method with a case study approach. The subjects consisted of 10 MI teachers who participated in lesson study training over three cycles, each comprising the stages of planning (plan), implementation (do), and reflection (see). Data were collected through observation, interviews, and documentation. The results indicate a significant improvement in teacher competencies, particularly in lesson planning, the application of active learning methods, classroom management, and conducting reflective practices. Teachers also demonstrated increased participation and collaboration in the joint learning process. The study concludes that the lesson study-based training model can serve as a strategic and sustainable alternative for developing the professional competence of MI teachers. The implications of this research highlight the need for institutional and policy support to integrate lesson study as a systemic component of teacher professional development in madrasah environments. ABSTRAK Kompetensi guru merupakan elemen kunci dalam menentukan kualitas pembelajaran, terutama di Madrasah Ibtidaiyah (MI) yang memiliki peran strategis dalam membentuk karakter dan kecerdasan siswa sejak dini. Namun, masih ditemukan kesenjangan antara kompetensi ideal guru dengan realitas di lapangan, terutama dalam aspek perencanaan pembelajaran, pengelolaan kelas, serta kemampuan refleksi. Penelitian ini bertujuan untuk mengkaji efektivitas model pelatihan berbasis lesson study dalam meningkatkan kompetensi profesional guru MI. Metode yang digunakan adalah metode kualitatif deskriptif dengan pendekatan studi kasus. Subjek penelitian terdiri dari 10 guru MI yang mengikuti pelatihan lesson study selama tiga siklus, yang masing-masing meliputi tahap perencanaan (plan), pelaksanaan (do), dan refleksi (see). Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam kompetensi guru pada aspek perencanaan pembelajaran, penerapan metode aktif, pengelolaan kelas, serta pelaksanaan refleksi pembelajaran. Guru juga menunjukkan peningkatan partisipasi dan kolaborasi dalam proses belajar bersama. Simpulan dari penelitian ini adalah bahwa model pelatihan berbasis lesson study dapat menjadi alternatif strategis dan berkelanjutan dalam pengembangan profesionalisme guru MI. Implikasi dari penelitian ini menunjukkan perlunya dukungan kelembagaan dan kebijakan untuk mengintegrasikan lesson study sebagai bagian dari pengembangan profesi guru secara sistemik di lingkungan madrasah.